Data Protection Heterogeneity in the European Union - Marko Hölbl (MDPI AG, 2021)
In light of digitalisation, we are witnessing an increased volume of collected data and data generation and exchange acceleration. Therefore, the European Union (EU) has introduced the General Data Protection Regulation (GDPR) as a new framework for data protection on the European level. However, GDPR allows the member states to change some parts of the regulation, and the member states can always build on top of the GDPR. An example is the collection of biometric data with electronic signatures. This paper aims to compare the legislation on data protection topics in the various EU member states. The findings show that the member states included in the study generally do not have many additional/specific laws (only in 29.4% of the cases). However, almost all have other/additional legislation to the GDPR on at least one topic. The most additional legislation is on the topics of video surveillance, biometry, genetic data and health data. We also introduce a dynamic map that allows for quick navigating between different information categories and comparisons of the EU member states at a glance.